Independent Professionals: Legal Issues and Challenges - Leighton, Patricia (Senate Hall, 2015)
Although Independent Professionals (IPros) have until recently been generally neglected by the academic community, including by specialists in both management and entrepreneurism, IPros cannot avoid being subject to key areas of regulation. This sometimes impacts upon them in a complex, controversial and unfair way. The regulatory framework contains key areas of fiscal policy, especially personal taxation, unfortunately often dominated by allegations of 'sham' relationships, the law relating to business associations, employment law and social protections. Some IPros are also subject to regulation by professional bodies. Virtually all of these areas of regulation present challenges, not least as IPros are hard to define and are not unambiguously a part of the business community or the labour market Keywords: Independent Professionals (IPROS), definition, regulation
Keywords: Independent Professionals (IPros)|definition|regulation